PAJAK PENGHASILAN BAGI OVER-THE-TOP DI INDONESIA: SEBUAH PELUANG DAN TANTANGAN - Cahyadini, Amelia; Muttaqin, Zainal; Dewi, Sinta; Sugiharti, Dewi Kania (Faculty of Law, Parahyangan Catholic University, 2022)
Over-the-Top (OTT) is a form of information technology innovation that is growing very rapidly, including in Indonesia as one of the largest OTT market country. OTT can earn income from users in Indonesia, while the right to tax this income cannot be imposed in Indonesia because OTT generally operates across national borders and does not have a permanent establishment in Indonesia. Therefore, it is necessary to consider income tax arrangements for OTT operating in Indonesia to provide legal certainty. This paper focuses on discussing the positive legal provisions of Income Tax that apply to OTT operating in Indonesia and the implementation of each of these regulations in the current era of economic digitalization. The author uses a normative juridical research method with a qualitative research approach. Based on this research, it is known that the provision of Income Tax for OTT does not yet exist, therefore the Government of Indonesia needs to design a national tax law that is able to accommodate income tax for OTT.